Аналіз розвитку ринку ресторанних послуг України в пострадянський період - Круль, Галина Ярославівна (ПП Іванюк, 2020)
Trends in the development of the restaurant business in the post-Soviet period are discussed in the article. The emergence of global and national fast service networks is noted in Ukraine. The most popular in recent years have been restaurants of national cuisine (especially oriental). The publication emphasizes the emergence of new types of restaurants: pubs, concept restaurants, specialized outlets for coffee and other food and beverages. The factors influencing the success of the restaurant business in the conditions of fierce competition are considered.
Keywords: ресторанні послуги; мережі швидкого харчування; національні мережі закладів ресторанного господарства; концептуальні ресторани; ресторани національних кухонь